Integration of Internet of Everything (IoE) in Precision Agriculture: A Case Study on Rice Commodity in West Java - Prahitaningtyas, Sherina (Journal of Agricultural Economy and Technology Development, 2025)
Technology-based precision agriculture is increasingly becoming a necessity in system the challenges of climate change, resource efficiency, and increased productivity. This study aims to analyze the implementation of the Internet of Everything (IoE) in precision agriculture systems on rice commodities in West Java. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and questionnaires with farmers and extension workers in three rice center districts: Indramayu, Subang, and Karawang. The results show that the application of IoE technologies such as soil sensors, automated irrigation systems, and land monitoring drones can increase water use efficiency by 30% and crop productivity by 17%. However, there are constraints in technology adoption including limited digital literacy, network infrastructure, and initial investment costs. This study concludes that the successful integration of IoE in precision agriculture requires the support of a technology ecosystem, continuous training, and inclusive government policies. This study contributes to the development of a strategy for data-driven agricultural digitalization in Indonesia.